The struggle for autonomy: a realist structural theory of international relations - Harknett, Richard J.; Yalçın, Hasan Basri (Wiley-Blackwell, 2012)
Harknett, Richard J. and Hasan B. Yalcin. (2012) The Struggle for Autonomy: A Realist Structural Theory of International Relations. International Studies Review, doi: 10.1111/misr.12010 Structural theories have advanced our understanding of International Relations (IR). This article contends that the two leading structural realist frameworks, however, rely too heavily on an ascribed unit motivation and core dynamic that are not derived from structure. This ultimately weakens both theories explanatory potential. This article offers a refinement called structural autonomy that explains IR through a focus on a self-reliant pursuit of autonomy and the particular distribution of capabilities found across the system.
WOS: 000312657000001